Effect of Melatonin for Regulating Mesenchymal Stromal Cells and Derived Extracellular Vesicles - Feng, Zi-Yi; Yang, Shu-De; Wang, Ting; Guo, Shu (Frontiers in Cell and Developmental Biology, 2021)
Melatonin is a hormone synthesized in the pineal gland, that primarily controls the body’s circadian rhythm. In recent years, melatonin has also been shown to regulate metabolism, provide neuroprotection, and act as an anti-inflammatory free radical scavenger. There has also been recent research interest in melatonin’s role in regulating mesenchymal stem cells (MSCs). MSCs are pivotal for their ability to differentiate into a variety of different tissues. There is also increasing evidence for the therapeutic prospects of MSCs via paracrine signaling. In addition to secreting cytokines and chemokines, MSCs can transfer mitochondria and secrete extracellular vesicles (EVs), allowing them to respond to injury and promote tissue regeneration. While there has been major research interest in the use of MSCs for regenerative medicine, clinical application is limited by many risks, including tumorigenicity, senescence, and sensitivity to toxic environments. The use of MSCs-derived EVs for cell-free therapy can potentially avoid the disadvantages of MSCs, which makes this an exciting prospect for regenerative medicine. Prior research has shown that MSCs via paracrine mechanisms can identify receptor-independent responses to melatonin and then activate a series of downstream pathways, which exert a variety of effects, including anti-tumor and anti-inflammatory effects. Here, we review the synthesis of melatonin, its mechanisms of action, and the effect of melatonin on MSCs via paracrine signaling. Furthermore, we summarize current clinical applications of melatonin and discuss future prospects.